Design a MATLAB-based system architecture for locating fiber fault in optical access network - Ng, Boon Chuan; Che Aziz, Siti Asma; Ab-Rahman, Mohammad Syuhaimi; Jumari, Kasmiran (2009)
This paper experimentally demonstrated a MATLAB-based graphical user interface (GUI) named Smart Access Network _Testing, Analyzing and Database (SANTAD) that able to measure the optical signal level, attenuation, losses, as well as detect any occurrence of fault and address the failure location in optical access network with point-to-multipoint (P2MP) configuration.This paper also presented a restoration mechanism scheme, where the protection mechanism for tree based optical switch will have capability to divert the signal onto protection line according to the types of failure condition and location of failures in access network.This will ensure the data flow continuously due to breakdown occur in the network and instantly repair the operation.The restoration scheme was simulated using OptiSystem, Inc. software in order to prove the solution feasibility.